PENGARUH VARIABEL KESEHATAN BANK TERHADAP KINERJA KEUANGAN BANK SYARIAH - Istiqomah, Anugrah Mega; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis researchis aimed to examine empirically the influence of bank health performance which consists of nonperformingfinancing, financing to deposit ratio, net operating margin, and the capital adequacy ratio offinancial performance which are measured by return on assets. This research uses quantitative data withpurposive sampling technique that produces 6 Syariah banking in Indonesia, and have published their quarterlyfinancial statements in 2012-2015 periods and havegot complete data associated with the variables which will bestudied.The data is the secondary data, the financial data has been obtained from the official website of BankIndonesia and the official website of the related bank. Tools such as SPSS 20 statistical test is used to determinethe multiple linear regression equation, the classic assumption test, the model feasibility test and hypothesis test.The result of this research indicates that non-performing financial (NPF) give significant and negativeinfluenceto the return on assets (ROA), it indicates that the rise in non-performing financing does not give anyinfluenceto the amount of return on assets whereas finance to deposit ratio (FDR), net operating margin (NOM)give positive and significant influenceto the return on assets (ROA), it indicates that the increase in finance todeposit ratio and net operating margin will increase the return on assets, whereas the capital adequacy ratio(CAR) give positive influence but not significant to the return on assets (ROA), itshows that the capitaladequacy ratio does not give any influence the return on assets.Keywords: Non-performing financing, finance to deposit ratio, net operating margin, capital adequacy ratio,return on assets.